Qualitative Analysis of Partnerships' Effect on Implementation of a Nationally Led Community-Based Initiative. Issue 5 (September 2018) - Garcia, Kristen M.; Martin, Emily; Garney, Whitney R.; Primm, Kristin M.
Introduction . The American Heart Association (AHA) was funded to implement a nationally led initiative to implement policy, systems, and environment (PSE) interventions in communities across the United States. In Cohort 1, 15 communities were tasked with working with local community partners to plan and implement initiatives. Method . Engaged as the evaluators, Texas A&M researchers conducted telephone interviews with project managers (employed by AHA) and community partners representing the 15 communities. Interviewees were asked questions pertaining to partnership planning and involvement in initiatives and overall perceptions of the impact of the program. Interviews were analyzed qualitatively using the Consolidated Framework for Implementation Research as the guiding framework. Results . Thematic analysis revealed that partners were used in planning and implementing initiatives and felt that initiatives were successful in building community engagement. Some noted success in PSE changes, although this was not a major focus of respondents, regardless of it being a main indicator for the funder. Discussion . Themes reveal several recommendations for those embarking on community-level work. Those recommendations include (1) build on existing priorities, (2) focus on incremental steps that build toward the bigger goal, (3) use national organizations to move more quickly, and (4) leverage resources through collaborative efforts.